1983
DOI: 10.1093/bja/55.5.371
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Sample Site on Blood Concentrations of Ici 35 868

Abstract: Simultaneous blood samples from an artery, a peripheral vein and a central vein were analysed for ICI 35868 concentrations following an induction dose of 2.0 mg kg-1 administered i.v. over 60 s, to five patients before cardiac surgery. Up to 60 s after the end of the administration of the drug there were wide differences in drug concentration between the sampling sites. Thus, any attempt to correlate effect with blood concentration over this early period would be problematic. From 60 s there were no significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 1 publication
1
12
0
Order By: Relevance
“…For phases in his profiles were often uninterpretable, the reason for which, we think, is venous sampling. The propofol, Major et al [28] measured significantly higher arterial than venous concentrations directly after bolus half-life of the additional early distribution phase in our study ranged from 0.1 to 0.6 min which is in agreement injection, which turned into the reverse after 1 min. Wang et al [29] found similar differences in an infusion with the findings of Adam et al [25], describing in some of the patients a half-life of this additional phase ranging setting.…”
Section: Induction Of Anaesthesia Pharmacokinetic Analysissupporting
confidence: 86%
See 1 more Smart Citation
“…For phases in his profiles were often uninterpretable, the reason for which, we think, is venous sampling. The propofol, Major et al [28] measured significantly higher arterial than venous concentrations directly after bolus half-life of the additional early distribution phase in our study ranged from 0.1 to 0.6 min which is in agreement injection, which turned into the reverse after 1 min. Wang et al [29] found similar differences in an infusion with the findings of Adam et al [25], describing in some of the patients a half-life of this additional phase ranging setting.…”
Section: Induction Of Anaesthesia Pharmacokinetic Analysissupporting
confidence: 86%
“…In general, arterial sampling is preferred when pharmacokinetic parameters are studied of drugs which are rapidly distributed, because the steeper arterial concentration profile provides a more sensitive measure for the detection of early distribution phases [ 26, 27]. For propofol, Major et al [ 28] measured significantly higher arterial than venous concentrations directly after bolus injection, which turned into the reverse after 1 min. Wang et al [ 29] found similar differences in an infusion setting.…”
Section: Discussionmentioning
confidence: 99%
“…Major et al . [18] found that there was no significant difference between arterial, central venous, and peripheral venous concentrations of propofol at sampling time beyond one minute.…”
Section: Discussionmentioning
confidence: 99%
“…And also, to be mixed instantaneously was a little difficult for high concentrations. [14] Therefore, high concentrations were still unable to predict ideal values. Maybe propofol at high concentration may follow nonlinear pharmacokinetics.…”
Section: Discussionmentioning
confidence: 99%